Semiotics of Gender Roles and Honour Killing in Pakistani Paintings - Mehvish Riaz (National University of Modern Languages (NUML), Islamabad, 2023)
The study examines how gender is represented through visual signs in the paintings on honour killing, how social structures gain meaning on getting painted, how power dynamics work in the so-called traditional or patriarchal societies, and if and how these semiotic constructions represent, underrepresent, or misrepresent Pakistani context. The grammar of the visual design of 40 paintings on honour killing, painted by male and female Pakistani painters belonging to different areas of Pakistan, have been qualitatively studied in the light of the theoretical understanding of ideational, interpersonal, and textual metafunctions suggested by Kress and van Leeuwen (2006). The visual grammar of the paintings suggests that the women have been represented as helpless, outcaste, oppressed, and marginalized, while men have, indirectly through visual signs, been depicted as oppressors and perpetrators. On the ideational level, society has also been highlighted as extremely oppressive and debilitating. Interpersonal metafunction reveals social negligence towards honour killing and female victimhood, while the textual orientation of the paintings not only suggests social control over the female body and choices as the core issue, but also highlights the strict condemnation of female oppression and honour killing by the painters.